2015
DOI: 10.1111/1475-6773.12281
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Antipsychotic Quality Reporting on Antipsychotic and Psychoactive Medication Use

Abstract: Objective. The objective of this study is to examine how nursing homes changed their use of antipsychotic and other psychoactive medications in response to Nursing Home Compare's initiation of publicly reporting antipsychotic use in July 2012. Research Design and Subjects. The study includes all state recertification surveys (n = 40,415) for facilities six quarters prior and post the initiation of public reporting. Using a difference-in-difference framework, the change in use of antipsychotics and other psycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…An international human rights group has identified a moral imperative for national governments to address overuse of psychotropic medications in older nursing home residents with dementia . The United States has used public reporting of antipsychotic utilization to facilitate reductions in psychotropic prescribing rates, an effort that increased medication reviews, reduced medication use, and increased use of nonpharmacological interventions . Spanish regulators might consider requiring public reporting of psychotropic medication use in care homes, an effort that might encourage uptake of the types of tools we studied, reduce overuse of such medications in a vulnerable population, and improve the quality and dignity of care provided to older Spanish citizens who are living with dementia.…”
Section: Discussionmentioning
confidence: 99%
“…An international human rights group has identified a moral imperative for national governments to address overuse of psychotropic medications in older nursing home residents with dementia . The United States has used public reporting of antipsychotic utilization to facilitate reductions in psychotropic prescribing rates, an effort that increased medication reviews, reduced medication use, and increased use of nonpharmacological interventions . Spanish regulators might consider requiring public reporting of psychotropic medication use in care homes, an effort that might encourage uptake of the types of tools we studied, reduce overuse of such medications in a vulnerable population, and improve the quality and dignity of care provided to older Spanish citizens who are living with dementia.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, an antipsychotic indicator similar to the CIHI indicator is reported. [108][109][110] Unlike the CIHI indicator, the presence of delusions or hallucinations is not an exclusion criteria, whereas bipolar disorder is. 109 The US Centers for Medicare and Medicaid Services has been publicly reporting information on LTC quality indicators since 2002, although public reporting of antipsychotics began only in 2012.…”
Section: Public Reportingmentioning
confidence: 99%
“…Bowblis et al [ 40 ] found that deficiency citation rates for NHs during a prior state inspection have an impact on AP use in response to the citation. Another analysis of the public reporting of AP use demonstrated a decline in use once the facility was subjected to reporting [ 41 ]. The ACA’s NH quality provisions emphasize transparency through public reporting of staffing and expenses [ 42 ].…”
Section: Policy Moving Forwardmentioning
confidence: 99%